A calculation method of biomass slagging rate based on crystallization theory. Issue 3 (5th December 2013) - Niu, Yanqing; Zhu, Yiming; Tan, Houzhang; Hui, Shien; Jones, Jenny M.; Liu, Yuanyi
ABSTRACT Aiming to the vacant research on slagging rate calculation of biomass, a method based on crystallization theory is proposed here. First, KCl–K2SO4–Na2SO4 ternary eutectic system, as main inducing factor of biomass slagging, is verified by slagging sample analysis, ternary eutectic experiment, and equilibrium calculation of FACTSAGE. Second, we assume that flue gas was solvent; the KCl–K2SO4–Na2SO4 ternary eutectic system and the refractory components were two solutes supersaturated in the solution. The slagging process is approximated as the combined effect of nucleation and solidification of the KCl–K2SO4–Na2SO4 eutectic system and the conglutination of the refractory components. Third, on the basis of nucleation rate equation, a formula for the slagging rate calculation is developed as J = k(Δcmax)m, where k defined as slagging constant is the empirical function of fly ash concentration and flue gas velocity, △cmax is the concentration difference of KCl + K3Na (SO4)2 in fly ash up and downstream of heating surfaces, and m is defined as slagging order, which is an empirical parameter dependent on the concentrations of KCl and K3Na(SO4)2. Meanwhile, an example is given on the calculation of m. However, additional experiments are required in order to improve the formulation of functions k and m. © 2013 Curtin University of Technology and John Wiley & Sons, Ltd.